2010
DOI: 10.1007/s10637-010-9533-0
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with Bevacizumab and standard chemotherapy restores abnormal immune parameters in advanced colorectal cancer patients

Abstract: Our study demonstrates that the abnormal immune parameters observed in metastatic CRC patients at presentation can substantially improve during treatment with either IFL or B-IFL. The immune parameters examined can provide a sensitive and valuable tool for monitoring immune function in CRC patients, and could be applied as surrogate markers predicting treatment-related outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…This phenomenon is linked to a decrease of Ki67 + expression in Tregs (25). In mCRC patients treated with bevacizumab, Manzoni et al revealed an increase of CD4, CD8 and CD3 lymphocyte numbers (29), whereas Tsavaris et al observed a better proliferation and cytokine production of circulating T-cells compared to patients treated with chemotherapy only (67). Moreover, the administration of anti-VEGF-A in tumor-bearing mice decreased PD-1 expression on intratumoral CD8 + T-cells and limited the co-expression of inhibitory checkpoints associated with exhaustion (44).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…This phenomenon is linked to a decrease of Ki67 + expression in Tregs (25). In mCRC patients treated with bevacizumab, Manzoni et al revealed an increase of CD4, CD8 and CD3 lymphocyte numbers (29), whereas Tsavaris et al observed a better proliferation and cytokine production of circulating T-cells compared to patients treated with chemotherapy only (67). Moreover, the administration of anti-VEGF-A in tumor-bearing mice decreased PD-1 expression on intratumoral CD8 + T-cells and limited the co-expression of inhibitory checkpoints associated with exhaustion (44).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…Evidence suggests that CPT-11-induced diarrhoea is an inflammation-mediated side effect, but the immunogen responsible remains unclear [20,[22][23][24]. To investigate whether CPT-11-induced diarrhoea was associated with the release of double-strand DNA (dsDNA), we first analysed clinical samples from CRC patients who received a CPT-11-based chemo-regimen treatment.…”
Section: Double-strand Dna Release Is Associated With Cpt-11 Treatmenmentioning
confidence: 99%
“…Whether the observed activity is caused by a special pharmacodynamic effect of bevacizumab in lymphangitic carcinomatosa remains speculative. Bevacizumab is known to exhibit immunomodulatory effects, 16,17 and the effects of trastuzumab partly depend on antibody-dependent cellular cytotoxicity, raising speculations about a resensitization toward trastuzumab. 18 In addition, the antipermeability activity substantially decreases tumorassociated edema in glioblastoma, leading to stable or improved neurologic function and quality of life in these patients.…”
Section: Discussionmentioning
confidence: 99%